Kesehatan Mental Ditinjau dari Kecemasan Akademik dan Dukungan Sosial Guru pada Siswa SMP Negeri 2 Gempol - Nizarotul Amalia Zahro; Estalita Kelly (KOLONI, 2026)
This study aimed to analyze the effects of academic anxiety and teacher social support on the mental health of students at SMP Negeri 2 Gempol. A quantitative approach with a correlational design was employed. The sample size consisted of 275 seventh- and eighth-grade students and was determined using the Slovin formula. Data were collected through a mental health scale, an academic anxiety scale, and a teacher social support scale and were subsequently analyzed using multiple linear regression. The results showed that academic anxiety and teacher social support simultaneously had a significant effect on students’ mental health, with a significance value below 0.001 and a coefficient of determination of 0.344. These findings indicate that the two variables explained 34.4 percent of the variation in students’ mental health. Partially, academic anxiety had a negative effect on mental health, whereas teacher social support had a positive effect. Teacher social support provided an effective contribution of 22.14 percent, which was greater than the 12.24 percent contribution of academic anxiety. The study concludes that higher academic anxiety is associated with poorer mental health, while stronger teacher social support is associated with better mental health among students.